Зброя раннього залізного віку з колекції Кам'янського історичного музею - Ляшко, Ю.Ю. (Археологія і давня історія України, 2019)
Статтю присвячено опису зразків зброї доби раннього заліза, які зберігаються в експозиції Історичного музею Кам'янського державного історико-культурного заповідника Черкаської обл. The article is sanctified to description of standards
of weapon twenty-four hours of early ferrous age, that
is kept in the display of historical museum of Kamyanka of state Historical and Cultural Center reserve of
the Cherkasy areal. In this paper, brief information is provided on similar
analogues of weapons that were found on the territory of Ukraine. But their short description is made. Particularly
worthy to highlight the Scythian sword-akinak, which is made in uncharacteristic for this type of form,
with a slightly curved blade and one-sided sharpening. This type of weapon is a unique achievement of weaponry
and dates from the second to the third quarter of the Vth century BC. Also at the end of the work there is
a conclusion regarding the existence of certain types of weapons in the Prytyasminsky region.